Analysis of IEC 61850 for a Reliable Communication System between Substations - Yang, Xin; Das, Narottam; Islam, Syed (University of Tasmania, 2013)
IEC 61850 Standard was introduced to address the challenge presented by existence of the multiple protocols in substation communications, which include many proprietary protocols; and to address the challenge introduced by legacy complicated substation from both cost and complicity. In this paper, the simulation results of different types of IEC 61850 network system configurations using OPNET Modeler simulation software were presented and the influence on data rate and delay characteristics of these system configurations were evaluated. The simulated results confirm that the ring configured system suitable for higher loading characteristics and higher system reliability.